The effects of nitrous oxide and surgical position on endotracheal tube cuff pressure, post operative hoarseness, and sore throat; a double-blind clinical trial - Gholamhassann Chaichi-Nosrati; Esmail Moshiri; Hesameddin Modir; Alireza Mohammadi (Annals of Thoracic Medicine)
BACKGROUND: The aim of this study was to evaluate the effects of nitrous oxide (N2O) and surgical position on endotracheal tube cuff (ETC) pressure, hoarseness, and sore throat (ST) after surgery under general anesthesia (GA). METHODS: This double-blind clinical trial was conducted on 212 candidates for surgery under GA. They were randomly allocated to four groups, namely a supine position group (Group S), a prone position group (Group P), a supine position and N2O group (Group SN), and a prone position and N2O group (Group PN). ST and hoarseness were assessed at recovery and 2, 4, 8, 12, and 24 h after surgery using a visual analog scale and a mild-to-severe scoring system, respectively. ETC pressure was also measured at 15, 30, 60, 90, and 120 min after surgery onset using an Ambu cuff pressure gauge. Moreover, the mean intraoperative propofol concentration was documented. The data were analyzed at a significance level of <0.05 and using the SPSS software (version 20.0). RESULTS: There was no significant difference among groups regarding surgery duration (P = 0.998), whereas ST and ETC pressure in Groups S and P were significantly less than Groups SN and PN (P = 0.001). Moreover, ST and ETC pressure in Group S were significantly less than the other groups (P = 0.001). None of the participants in Groups S and P had hoarseness, and there was a significant difference among the four groups regarding the frequency of hoarseness (P = 0.001). Moreover, none of the participants in Group SN needed postoperative analgesic, and there was no significant difference between Groups S and P regarding postoperative analgesic use (P = 0.998). Intraoperative propofol use in Group SN was significantly less than the other groups (P = 0.001). CONCLUSION: ETC pressure should periodically be monitored and adjusted during lengthy surgeries in prone position and N2O anesthesia to prevent postoperative ST and hoarseness.